O16.3 Cytokine immune response against natural human papillomavirus infection among men in kisumu, kenya. (14th July 2019) - Ondondo, Raphael; Bukusi, Elizabeth; Nganga, Zipporah; Kiptoo, Michael; Mpoke, Solomon
Abstract : Background: Human papillomavirus (HPV) is strongly associated with ano-genital and cervical cancer. Persistence of oncogenic HPV genotypes is required for development and progression of HPV-associated malignancies. Although, >70% of women clear incident HPV infections, data on natural history and HPV immunology among men is limited. Methods: To evaluate cell-mediated immune response against natural HPV infection among men, we assessed cytokine (IFN-γ, TNF-α, IL-2, IL-4, IL-6, IL-10 and IL-13) responses in peripheral-blood-mononuclear cells (PBMCs) collected from 135 men enrolled in a prospective HPV cohort study. PBMCs were stimulated by HPV L1 gene viral-like-particles (VLP) and cytokine responses measured using a multiplex Luminex assay. Results: Of 135 men included in this analysis, 41 men had persistent HPV infection, 44 men cleared HPV infection and 50 were HPV uninfected. Their mean (SD) ages were 28.9 (6.79), 27.6 (6.49) and 26.4 (4.81) years respectively. Immune response was induced in 22% (95% CI: 12.8–35.2) of HPV uninfected men, 64% (95% CI: 48.9–76.2) of men with HPV clearance and 51% (95% CI: 36.5–65.8) of men with HPV persistence. Men with HPV clearance and HPV persistence were significantly (p<0.01) at increased odds [OR = 6.20 (95% CI: 2.29–17.19) and OR = 3.72 (95% CI: 1.37–10.25) respectively] of mounting cytokine responses compared to HPV uninfected men. T-helper type 1 (Th1) cytokines IFN-γ (5.1 mean-fold increase) and IL-2 (4.2-fold) were significantly (p<0.0001) upregulated among men with HPV clearance and not in men with HPV persistence, compared to HPV uninfected men. Among men with HPV clearance compared to those with persistent HPV infection, IFN-γ (2.4–fold) and IL-2 (3.0-fold) were the only cytokines significantly (p<0.0001) upregulated. In the three groups of men, there were no significant changes in Th1 cytokine TNF-α, and Th2 cytokines: IL-4, IL-6, IL-10 and IL-13. Conclusion: In this study, Th1 cell-mediated cytokine immune response was associated with HPV clearance in men. Disclosure: No significant relationships.